"Theism, Naturalism, and Meta‐Ethics". Issue 4 (13th March 2013) - Jordan, Matthew C.
Abstract The relationship between God and morality has been a topic of philosophical discussion since Socrates engaged Euthyphro in the agora. In recent years, it has received a lot of attention, as theistic philosophers have attempted to show that divine command theory and other theistic meta‐ethical accounts are defensible. Whether metaphysical naturalism is compatible with moral realism is a related (and equally controversial) topic. This essay surveys the main issues in these debates.